Metal ions accelerated phytosterol thermal degradation on Ring A & Ring B of steroid nucleus in oils. (October 2017) - Hu, Yinzhou; Huang, Weisu; Li, Maiquan; Wang, Mengmeng; Zhao, Yajing; Xu, Tao; Zhang, Liuquan; Lu, Baiyi; He, Yan
Abstract: This study aimed to investigate the effect of metal ions on the degradation of phytosterols in oils. The oil was heated at 180 °C for 1 h with/without addition of Fe 3 +, Fe 2 +, Cu 2 +, Mn 2 +, Zn 2 +, Na +, Al 3 + and Mg 2 + . Variations of β-sitosterol, stigmasterol, campesterol, brassicasterol and their degradation products were confirmed by the GC–MS analysis. In general, the increase of the metal ion concentration resulted in more phytosterol degradation, and the ability of metal ions following decreasing order: Fe 3 +  > Fe 2 +  > Mn 2 +  ≥ Cu 2 +  ≥ Zn 2 +  > Na +  ≥ Mg 2 +  > Al 3 + . Metal ions significantly induced phytosterol autoxidation on C5, C6 and C7 on Ring B of steroid nucleus at even a low concentration, and induced dehydration on the C3 hydroxyl to form dienes and trienes at high concentration. The metal ions in oils are accounted for increasing phytosterol degradation, which decreases food nutritional quality and gives rise to the formation of undesirable compounds. Graphical abstract: Highlights: The effects of metal ions on the degradation of phytosterols were investigated. Metal ions induced phytosterol oxidation on C5, C6 and C7. Ferric ion induced dehydration on the C3 hydroxyl to form dienes and trienes at high concentration.